The Influence of Principal Supervision on Learning Quality through Teachers' Professional Competence - Suwari; Qonita Gita Praha Zulham Akhmad (Managere: Indonesian Journal of Educational Management, 2025)
This study examines the influence of principal supervision and teachers' professional competence on Islamic Religious Education (PAI) learning quality in State Junior High Schools throughout Lumajang Regency. The background of this research is motivated by the low quality of learning in Indonesia, which is reflected in the results of international competency tests such as PISA. This study aims to examine whether the principal's supervision and teachers' professional competence significantly affect the quality of PAI learning. The approach was quantitative research with a correlational design, involving 65 PAI teachers in State Junior High Schools in Lumajang Regency as respondents. The sampling technique used total sampling, and data analysis was carried out by multiple linear regression to test the relationship between the variables studied. The results of the analysis showed that the supervision of the principal had a positive and significant influence on the quality of learning (β = 0.589, p < 0.05), while the professional competence of teachers had a negative influence on the quality of learning (β = -0.358, p < 0.05). These findings have implications for the development of educational leadership theories and evidence-based education policies by suggesting that strengthening the supervision of school principals should be a priority in improving the quality of learning in schools.